Implementing evidence into practice to improve chronic lung disease management in Indigenous Australians: the breathe easy, walk easy, lungs for life (BE WELL) project (protocol) - David P. Meharg; Christine R. Jenkins; Graeme P. Maguire; Stephan Jan; Tim Shaw; Sarah M. Dennis; Zoe McKeough; Vanessa Lee; Kylie G. Gwynne; Debbie McCowen; Boe Rambaldini; Jennifer A. Alison (BMC Pulmonary Medicine, 2022)
Abstract Background Strong evidence exists for the benefits of pulmonary rehabilitation (PR) for people with chronic obstructive pulmonary disease (COPD), however the availability of culturally safe PR for Aboriginal and Torres Strait Islander (Indigenous) Peoples is limited. The study aims to determine whether PR can be implemented within Aboriginal Community Controlled Health Services (ACCHS) to improve outcomes for Indigenous people with COPD. Methods Multi-centre cohort study using participatory action research guided by the Knowledge-to-Action Framework. ACCHS supportive of enhancing services for chronic lung disease will be recruited. Aboriginal Health Workers (AHW) and the exercise physiologist (EP) or physiotherapist (PT) within these ACCHS will attend a workshop aimed at increasing knowledge and skills related to management of COPD and the provision of PR. Indigenous people with COPD will be invited to attend an 8-week, twice weekly, supervised PR program. Outcomes: AHW, EP/PT knowledge, skills and confidence in the assessment and management of COPD will be measured before and immediately after the BE WELL workshop and at 3, 6 and 12 months using a survey. PR participant measures will be exercise capacity (6-minute walk test (6MWT), health-related quality of life and health status at commencement and completion of an 8-week PR program. Secondary outcomes will include: number, length and cost of hospitalisations for a COPD exacerbation in 12-months prior and 12-months post PR; local contextual factors influencing implementation of PR; specific respiratory services provided by ACCHS to manage COPD prior to project commencement and at project completion. Repeated measures ANOVA will be used to evaluate changes in knowledge and confidence over time of AHWs and EP/PTs. Paired t-tests will be used to evaluate change in patient outcomes from pre- to post-PR. Number of hospital admissions in the 12 months before and after the PR will be compared using unpaired t-tests. Discussion Pulmonary rehabilitation is an essential component of best-practice management of COPD and is recommended in COPD guidelines. Indigenous peoples have limited access to culturally safe PR programs. This study will evaluate whether PR can be implemented within ACCHS and improve outcomes for Indigenous people with COPD. Trial registration Australian New Zealand Clinical Trials Registry (ANZCTR) ACTRN12617001337369, Registered 2nd September 2017 https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=373585&isClinicalTrial=False